2009
DOI: 10.1590/s1516-31802009000300007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of prognostic factors for cancer of the uterine cervix after radical hysterectomy

Abstract: CONTEXT AND Objective: Cancer of the uterine cervix is still very common in Brazil. It is important to evaluate factors that influence its prognosis. The aim here was to analyze the prevalence of prognostic anatomoclinical factors among patients with carcinoma of the uterine cervix undergoing radical hysterectomy. DESIGN AND SETTING:Cross-sectional study on 301 patients with invasive carcinoma of the uterine cervix who underwent Level III Piver-Rutledge hysterectomy surgery at São Marcos Hospital. METHODS:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
6
1
6
Order By: Relevance
“…Some authors found the incidence of cervical PSI to be 12.5%, 27% and 35.1% respectively. [13][14][15] These figures are distinctly higher than findings reported by Memarzadeh et al in a group of parametrial PSI. We may speculate that parametrial PSI constitutes the next step of cervical PSI.…”
Section: Discussioncontrasting
confidence: 61%
“…Some authors found the incidence of cervical PSI to be 12.5%, 27% and 35.1% respectively. [13][14][15] These figures are distinctly higher than findings reported by Memarzadeh et al in a group of parametrial PSI. We may speculate that parametrial PSI constitutes the next step of cervical PSI.…”
Section: Discussioncontrasting
confidence: 61%
“…por orientar e divulgar os agravos que mais acometem a sua região, como prevenir e buscar estratégias e possibilidade de tratamento com o uso de tecnologias apropriadas a cada caso e com o objetivo de resolver problemas, diminuindo o sofrimento dessa população (TAVARES et al, 2009).…”
Section: Considerações Finaisunclassified
“…Atualmente, a IARC (Agência Internacional para Pesquisa de Câncer) divide os HPVs em de baixo risco oncogênico (HPV-6, 11, 40, 42, 43, 44, 54, 61, 70, 72 e 81) e de alto risco oncogênico (HPV- 16,18,31,33,35,39,45,51,52,56,58,59,68, 73 e 82) de acordo com a sua capacidade de gerar neoplasias malignas (14) . Os tipos HPV- 26,53,66,67,68,70, 73 e 82 são classificados como genótipos de provável alto risco (14,31,32) .…”
Section: Epidemiologia Do Hpvunclassified
“…O tratamento primário para câncer do colo do útero, que pode ser por cirurgia ou radioterapia, com ou sem quimioterapia sensibilizante, possui uma taxa de cura de cerca de 80% a 95% em pacientes diagnosticadas com a doença em estadio inicial (estadios I e II) e aproximadamente 60% em pacientes com estadio III da doença (6) . A histerectomia simples ou radical e linfadenectomia pélvica é o tratamento de escolha em estadios iniciais (IA1, IA2, IB1, IB2, IIA1 ou 2, IIB) (58,59) .…”
Section: Tratamento Do Câncer Do Colo Do úTerounclassified
See 1 more Smart Citation